What determines trust? Human capital vs. social institutions. Evidence from Manila and Moscow - John V. C. Nye; Gregory Androuschak; Desiree Desierto; Garett Jones; Maria Yudkevich (University of the Philippines, School of Economics (UPSE), 2012)
It is now well established that highly developed countries tend to score well on measures of social capital and have higher levels of generalized trust. In turn, the willingness to trust has been shown to be correlated with various social and environmental factors (e.g. institutions, culture) on one hand, and accumulated human capital on the other. To what extent is an individual's trust driven by contemporaneous institutions and environmental conditions and to what extent is it determined by the individual's human capital? We collect data from students in Moscow and Manila and use the variation in their height and gender to instrument for measures of their human capital to identify the causal effect of the latter on trust. We find that human capital positively affects the propensity to trust, and its contribution appears larger than the combined effect of other omitted variables including, plausibly, social and environmental factors.
Keywords: 330; Vertrauen; Humankapital; Social Capital; Institutionelle Infrastruktur; Studierende; Moskau; Manila